Recognition of Radionuclides were Released from Fukushima Daiichi Nuclear Power Plant Accident: Mothers who Continue Voluntary Evacuation - Matsunaga, Hitomi (Journal of Japan Society of Nursing Research, 2020)
Aim: The aim of this study was to reveal the recognition of radiation materials to the mothers who continue voluntary evacuation. Methods: Semi-structured interviews were conducted with twenty-seven mothers. Data were analyzed using content analysis. Results: Recognition of radiation materials released by the Fukushima Daiichi Nuclear Power Plant Accident were classified into seven categories: "Materials was negative effects on our health" "My perception of materials different from laypeople" "Materials destroyed natural environment" "Materials didn't stay one spot" "Materials negative effects were continue for a long time" "Materials was not equally exist by each environment" "Materials effects can be reduced". Discussion: To support the mothers who have anxiety about radionuclides, it is essential to considering they had various recognition about radionuclides. Furthermore, it is important to deeply understand the wishes that they want to avoid even slightly exposure of their children due to Fukushima Daiichi Nuclear Power Plant accident.